Fatigue and depression in multiple sclerosis: pharmacological and non‐pharmacological interventions. (September 2016) - Brenner, P.; Piehl, F.
Abstract : Multiple sclerosis (MS) is a neuroinflammatory condition with a prominent progressive neurodegenerative facet that typically affects young‐ or middle‐aged adults. Although physical disabilities have been in the foreground by being easier to assess, there is an increasing interest in mental disabilities and psychiatric co‐morbidities, which have a disproportionally high impact on important outcome measures such as quality of life and occupational disability. In particular, cognitive impairment, depression and mental fatigue, which mutually interact with each other, seem to be of importance in this context. In recent decades, major efforts have been invested in developing more effective disease modulatory treatments. This has resulted in novel therapeutic options and awareness of the importance of early intervention. In comparison, good quality and adequately powered studies on symptomatic treatments of fatigue and psychiatric co‐morbidities in MS are rare, and awareness of treatment options is much lower. We here review the existing evidence base for symptomatic treatment of fatigue and depression in MS patients. With regard to fatigue, off‐label prescription of alertness improving drugs is common, in spite of all but absent evidence of efficacy. In contrast, a number of smaller studies suggest that physical exercise and fatigue management courses may have some clinical benefit. Very few studies have addressed the efficacy of antidepressants and non‐pharmaceutical interventions specifically in MS patients. Therefore, treatment guidelines largely rely on data from non‐MS populations. In the future, there is a strong motive to direct additional resources to the study of these important aspects of MS.